Adsorption of Ciprofloxacyn by Plate-Like Bi4Ti3O12 - Manunggal, Pinky Lintang Satriani; Prasetyo, Anton (ALCHEMY:Journal of Chemistry, 2025)
Antibiotic compound waste has attracted significant attention because of its harmful effects on aquatic environments. One of the methods reported as a potential approach for antibiotic wastewater treatment is adsorption. Bi4Ti3O12 is a triple-layer Aurivillius compound reported to exhibit adsorption properties, although research remains limited. Therefore, we synthesized plate-like Bi4Ti3O12 using the molten salt method. The adsorption test results showed that Bi4Ti3O12 reduced ciprofloxacin concentration by ~51% within 120 minutes. It shows that Bi4Ti3O12 has the excellent capability to adsorb the antibiotic compound ciprofloxacin. Keywords: Ciprofloxacin, Adsorption, Bi4Ti3O12